2013
DOI: 10.9755/ejfa.v25i1.15395
|View full text |Cite
|
Sign up to set email alerts
|

Potassium dynamics in three alluvial soils differing in clay contents

Abstract: Despite the presence of a huge amount of potassium (K +

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
14
0

Year Published

2016
2016
2021
2021

Publication Types

Select...
4
2
1

Relationship

1
6

Authors

Journals

citations
Cited by 27 publications
(15 citation statements)
references
References 12 publications
(7 reference statements)
1
14
0
Order By: Relevance
“…Further, soil response to applied K is different than N and P which is diverse (Wakeel et al, 2013). Farmers' education about potassium application and its effects on different crop mechanisms and productivity are needed.…”
Section: Lack Of Awareness About Balanced Fertilizer Use Conceptmentioning
confidence: 99%
See 3 more Smart Citations
“…Further, soil response to applied K is different than N and P which is diverse (Wakeel et al, 2013). Farmers' education about potassium application and its effects on different crop mechanisms and productivity are needed.…”
Section: Lack Of Awareness About Balanced Fertilizer Use Conceptmentioning
confidence: 99%
“…Adequate supply of K improves the osmotic adjustment and develops tolerance in plants to water deficit (Egilla et al, 2005). Likely, many researches on potassium function to improve salt stress are available (Cakmak, 2005;Ashraf et al, 2012;Wakeel et al, 2013). Potassium minimizes the detrimental effects of sodium (Na) under salt stress by improving K: Na ratio in plant tissue and plant cell (Wakeel et al, 2013).…”
Section: Soil Sustainability and Abiotic Stressesmentioning
confidence: 99%
See 2 more Smart Citations
“…The lowest (2807.2 mg kg -1 ) amount of total-K was noticed at Rajgarh tehsils of Churu district which may be ascribed to sandstone type parent material and their degree of weathering (Ahmed;and Walia, 1999). Recently, it has been reported that the presence of specific clay minerals affect the K-fixing capacity and slow and fast release of K in different soils (Wakeel et al, 2013). Smectite along with the mica is the reason for a soil having appreciable amount of total-K. Only 1 -2% of the total soil K is in a readily available form.…”
Section: Total K (Total-k)mentioning
confidence: 99%